1991
DOI: 10.1111/j.1475-6765.1991.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Support for gender equality in West Europe

Abstract: Abstract. This paper examines attitudes to the role of women in the public and private spheres among West European men and women. There are inter‐country differences that are partly explained by history, politics, and religion. There are also consistent gender differences in these attitudes, a finding quite different from that in the U.S. Over time, gender role attitudes have become more egalitarian. The sources of these changes seem to be changing attitudes of individuals toward the public role of women, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Data from Western Europe and the United States indicate that individuals with more conservative political ideology tend to have more traditional attitudes toward sex, marriage, and gender roles (Lesthaeghe and Meekers 1986;Lottes and Kuriloff 1992;Mason and Lu 1988;Wilcox 1991). Most of these relationships have been observed for nationally representative samples in analyses with controls for confounding factors.…”
Section: Previous Evidencementioning
confidence: 87%
See 1 more Smart Citation
“…Data from Western Europe and the United States indicate that individuals with more conservative political ideology tend to have more traditional attitudes toward sex, marriage, and gender roles (Lesthaeghe and Meekers 1986;Lottes and Kuriloff 1992;Mason and Lu 1988;Wilcox 1991). Most of these relationships have been observed for nationally representative samples in analyses with controls for confounding factors.…”
Section: Previous Evidencementioning
confidence: 87%
“…This paper focuses on one important type of characteristic which may influence attitudes toward family and gender roles, namely general values and beliefs. Previous studies have shown that, in Western Europe and the United States, religiosity is an important correlate of a wide range of traditional attitudes toward cohabitation, family and gender roles (e.g., Felty and Poloma 1991;Luker 1984;Lesthaeghe and Meekers 1986;Lesthaeghe and Surkyn 1988;Mason and Bumpass 1975;Mason and Lu 1988;Thornton and Freedman 1979;Thornton 1985;Thornton, Alwin, and Camburn 1983;Thornton, Axinn, and Hill 1992;Wilcox 1991). In addition, previous researchers have hypothesized that attitudes toward family and gender roles may be related to other general values and beliefs, such as consumerism, concern with individual autonomy and personal fulfillment, and political ideology Crimmins 1988, 1991;Crimmins, Easterlin, and Saito 1991;Lesthaeghe and Meekers 1986;Lesthaeghe and Surkyn 1988;Thornton 1989).…”
mentioning
confidence: 99%
“…After the Second World War the percentage of Italian women in the labour market fell, reaching the lowest levels in Western Europe (Ginsborg, 1990: 244). Increasingly confined to the domestic sphere during the 1950s and 1960s, Italian women lived in a society whose higher religiosity and lower educational levels made support for gender equality weak by comparison with other Western European countries (Wilcox, 1991). Does the balance of parental influence shift away from the mother in a more patriarchal society?…”
Section: The Cattaneo Study and Methods Of Analysismentioning
confidence: 99%
“…This analysis first identifies factors that predict the likelihood that women experience each type of subjective discrimination. While little research has looked directly at the causes of subjective discrimination, considerable research has examined the relationship between various factors and women's attitudes toward related issues such as sex roles and consciousness about inequality (see, for example, Ransford and Miller 1983;Thornton, Alwin, and Cambum 1983;Gurin 1985;Gruber and Bjorn 1988; Davis and Robinson 1991;Harlan and Weiss 1982;Wilcox 1991;Banaszak and Plutzer 1993). This research lends initial support to the hypothesis that the likelihood of a woman to experience subjective discrimination may be predicted based on a variety of independent variables.…”
Section: Expectationsmentioning
confidence: 99%